Research trends between acquired immune deficiency syndrome and hematological malignancies: a bibliometric analysis - Qiwen Zhou; Hao Sun; Shanshan Fan; Lan Luo; Jianhua Ji; Zejiao Jiang; Haiyan Min (Discover Oncology)
Abstract Objective This study examines the well-documented association between HIV/AIDS and hematological malignancies, where HIV infection increases the risk of developing these conditions, using bibliometric analysis to explore research trends and global patterns. Methods A bibliometric analysis was performed using the Web of Science Core Collection database, focusing on English-language articles related to “HIV/AIDS” and “hematological malignancies” published from 1979 to August 2024, employing VOSviewer, CiteSpace, and R package “Bibliometrix” for data analysis and visualization. Results A total of 1336 relevant articles were identified, with the United States as the leading contributor, followed by China. Prominent research institutions included the Université Paris Cité, publique hopitaux paris (APHP) and Harvard University. Blood is the most influential journal in this field, while authors Elie Azoulay and Hans-Peter Kiem were noted as influential figures. Keyword analysis highlighted bone marrow transplantation, lymphoma, and epidemiology as key research areas. Conclusion This study analyzed the evolving research landscape, hotspots, and trends in HIV/AIDS and hematological malignancies. Our findings reveal a critical shift from managing acute infections to focusing on long-term clinical outcomes, highlighting the paramount importance of continued emphasis on precise diagnostics, personalized treatment strategies, and optimized interventions like bone marrow transplantation to improve patient prognosis and survival.